PERLINDUNGAN HUKUM TERHADAP HAK-HAK TENAGA KERJA MENURUT QANUN NOMOR 7 TAHUN 2014 TENTANG KETENAGAKERJAAN - Endro Prakoso; Marzuki Marzuki; Mustamam Mustamam (Jurnal Ilmiah METADATA, 2021)
The rights of workers according to Qanun Number 7 of 2014 generally refer to Law Number 13 of 2003 concerning Manpower. However, at certain points, there are differences in substance, namely in relation to protection and “meugang” holiday time to welcome Ramadan, Eid al-Fitr and Eid al-Adha, there are also holidays commemorating the Tsunami and the rights of workers / laborers to receive meugang allowances to welcome Ramadan and Eid al-Adha. The weakness of the protection of workers' rights in Qanun Number 7 of 2014, which is related to the obligation of companies and entrepreneurs to provide Meugang allowances in Article 48 of the Qanun which are unclear and firm. Another weakness, namely the provisions of Article 66 and Article 67 of the Qanun, which involves workers / laborers in implementing corporate social responsibility. It can be said that the legal provisions regarding the protection of workers / labor rights in Qanun Number 7 of 2014 concerning Manpower, can be said that it has not guaranteed certainty and justice.